Implementasi video interaktif “susi” (suami siaga) dalam meningkatkan kesiapan suami sebagai birth companion - Hasriani, Hasriani; Sampara, Nurqalbi; Asniar, Asniar (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Anxiety is a common psychological response experienced by pregnant women approaching childbirth. This condition requires optimal social support, especially from the husband as the primary companion during pregnancy and labor. Husbandly support reflects attention, concern, and responsibility for the wife's health and well-being. Purpose: To analyze the implementation of the “susi” interactive (standby husband) video in improving husbands' readiness as birth companions. Method: A quasi-experimental study using a one-group pretest–posttest design. A sample of 30 participants, husbands of pregnant women in their third trimester, was selected using a purposive sampling technique. The intervention consisted of a screening of the “susi interactive video (standby husband). Data were analyzed using SPSS 25 with the McNemar test. Results: The study showed a significant difference between husbands' readiness before and after the video intervention (p-value 0.000 = <0.05). Conclusion: The family-based “susi” interactive video effectively improves husbands' knowledge and readiness to accompany childbirth. This intervention strengthens the husband's understanding of his role, emotional-physical support, and involvement in decision-making, potentially supporting the mother's psychological well-being and ensuring a smooth delivery. Keywords: Childbirth Assistance; Family Support; Husband Readiness; Standby Husband. Pendahuluan: Kecemasan merupakan salah satu respons psikologis yang umum dialami ibu hamil menjelang persalinan. Kondisi ini memerlukan dukungan sosial yang optimal, khususnya dari suami sebagai pendamping utama selama kehamilan dan proses persalinan. Dukungan suami mencerminkan bentuk perhatian, kepedulian, serta tanggung jawab terhadap kesehatan dan kesejahteraan istri. Tujuan: Untuk menganalisis implementasi video interaktif “susi” (suami siaga) dalam meningkatkan kesiapan suami sebagai birth companion. Metode: Quasi eksperimen dengan pendekatan one group pretest–posttest design. Sampel berjumlah 30 partisipan yang merupakan suami dari ibu hamil trimester III, dipilih menggunakan teknik purposive sampling. Intervensi yang diberikan berupa pemutaran video interaktif suami siaga. Analisis data menggunakan SPSS 25 dengan uji Mc. Nemar. Hasil: Menunjukkan perbedaan signifikan antara kesiapan suami sebelum diberikan intervensi video dan setelah diberikan intervensi (p value 0.000 = <0.05). Simpulan: Video interaktif suami siaga berbasis keluarga efektif meningkatkan pengetahuan dan kesiapan suami dalam mendampingi persalinan. Intervensi ini memperkuat pemahaman peran suami, dukungan emosional-fisik, serta keterlibatan dalam pengambilan keputusan, sehingga berpotensi mendukung kondisi psikologis ibu dan kelancaran persalinan. Kata Kunci: Dukungan Keluarga; Kesiapan Suami; Pendampingan Persalinan; Suami Siaga.